2019
DOI: 10.1038/s41598-019-53134-0
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin enhances cisplatin sensitivity of resistant non-small cell lung carcinoma stem-like cells by targeting mTOR-Akt axis to repress migration

Abstract: Conventional chemotherapeutic regimens are unable to prevent metastasis of non-small cell lung carcinoma (NSCLC) thereby leaving cancer incurable. Cancer stem cells (CSCs) are considered to be the origin of this therapeutic limitation. In the present study we report that the migration potential of NSCLCs is linked to its CSC content. While cisplatin alone fails to inhibit the migration of CSC-enriched NSCLC spheroids, in a combination with non-steroidal anti inflammatory drug (NSAID) aspirin retards the same. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 57 publications
3
20
0
Order By: Relevance
“…The combination was effective at decreasing drug resistance, stemness, and hypoxia in TME. Most of our results are in line with recent literature 20,21 …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The combination was effective at decreasing drug resistance, stemness, and hypoxia in TME. Most of our results are in line with recent literature 20,21 …”
Section: Discussionsupporting
confidence: 93%
“…Most of our results are in line with recent literature. 20,21 In cisplatin-resistant cell lines, the increased activation of ALDH1 is related to the expression of tumor stem cell markers. 22 Lung cancer cells expressing CD44 are enriched for stem-like properties, and CD44-positive cells show a higher level of expression for pluripotency markers (Oct-4, Sox-2) and increased resistance to cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we investigated the effects of COX-2 of an array of known pro-oncogenic signaling pathways. We observed robust AKT activation in COX-2 overexpressing cells and a loss of MMP expression and PI3K signaling upon COX-2 silencing confirming a role for MMPs and AKT in NSCLC metastasis occurrence and development [40][41][42][43]. We further demonstrated the ability of COX-2 to bind to the EGFR which, in turn, activated EGFR and enhanced PI3K signaling.…”
Section: Surgicalsupporting
confidence: 67%
“…A study has shown that aspirin, by downregulation of GLUT1 and weakening glucose uptake as well as reducing the level of oxidizing species, decreases the growth of liver cancer cells (Y. Liu, Feng, et al, 2019). Aspirin can attenuate AKT/mTOR signaling in lung carcinoma cells that in turn causes impairment of Wnt/Bcatenin signaling pathway (Khan et al, 2019). As presented in Figures 2 and 3, these signaling pathways have considerable effects on metabolism.…”
Section: Metabolism As Target For Cancer Treatmentmentioning
confidence: 99%